Effects of monosaccharides on in vitro neutral detergent fibre digestibility and the associated ruminal bacterial communities - Nampasa, Mercy (Stellenbosch : Stellenbosch University, 2019)
Thesis (MScAgric)--Stellenbosch University, 2019.